The Relationship Between Foot Exercise and Neuropathy Scores Among Diabetic Neuropathy Patients in Indonesia: A Scoping Review - Satria Akbar Putra Asmara; Ulil Albab Habibah; Muhammad Wicaksana Suryadi; Nazla Fahnaz Aufar; Jihan Irbah Salsabila (Universitas Pahlawan Tuanku Tambusai, 2026)
Diabetic neuropathy (DN) is one of the most common complications in patients with type 2 diabetes mellitus. Its prevalence has increased in Indonesia in parallel with the rising national prevalence of type 2 diabetes mellitus. Foot exercise is recommended as a simple non-pharmacological intervention for Diabetic neuropathy (DN); however, existing evidence remains fragmented. This study aimed to map the effectiveness of foot exercise in reducing neuropathy scores among patients with diabetic neuropathy in Indonesia. A scoping review was conducted on articles published between 2016 and 2026 from Garuda, Google Scholar, PubMed, and EBSCO databases. Study selection followed the PRISMA framework with strict inclusion and exclusion criteria. A total of 7 studies were analyzed using a descriptive narrative approach. All studies demonstrated a significant reduction in neuropathy scores (p<0.05) following foot exercise interventions, assessed using both subjective (DNS) and objective instruments (DNE, MNSI, TCSS). Intervention duration ranged from 1 to 24 weeks, with frequencies varying from 3 times per week to 5 times per day. More optimal outcomes were observed with longer durations or higher frequencies of intervention. Foot exercise is effective in reducing neuropathy scores in patients with diabetic neuropathy by improving blood circulation, tissue oxygenation, and insulin sensitivity. Regular implementation with adequate duration and frequency yields optimal outcomes and is recommended as a safe and simple non-pharmacological therapy.